The Helicobacter pylori single nucleotide polymorphisms SNPs associated with multiple therapy resistance in Colombia - Guzman, Kevin; Montenegro, Lidia; Pazos, Alvaro (Frontiers in Microbiology, 2023)
The Helicobacter pylori (H. pylori) eradication using multiple therapies is used as prevention strategy, its efficacy has been altered by the emergence of single nucleotide polymorphisms in genes associated to H. pylori multiple antibiotics resistance. To estimate antibiotic resistance rates associated to mutations in H. pylori genes in high cancer risk population in Colombia, We included 166 H. pylori whole genome sequences from a cohort of individual having a high risk of gastric cancer. By using the reference strain ATCC 26695, we identified mutations in specific genes to evaluate resistance rates for different antibiotics: 23S rRNA for clarithromycin, 16S rRNA for tetracycline, pbp1A for amoxicillin, gyrA for levofloxacin, and rdxA for metronidazole. The phylogenomic analysis was conducted using the core genome consisting of 1594 genes of H. pylori-ATCC 26695. Our findings revealed that the resistance rate of H. pylori to clarithromycin was 3.62%, primarily associated with mutations A2143G and A2142G in the 23S rRNA gene. For tetracycline, the resistance rate was 7.23%, with mutations A926G, A926T, and A928C observed in the 16S rRNA gene. Amoxicillin resistance was found in 25.9% of cases, with observed mutations in the pbp1A gene including T556S, T593, R649K, R656P, and R656H. In the gyrA gene, mutations N87K, N87I, D91G, D91N, and D91Y were identified, resulting in a resistance rate of 12.04% to levofloxacin. The most common mutations in the rdxA gene associated with metronidazole resistance were a stop codon, and mutations at D59N and D59S, resulting in a resistance rate of 99.3%. The high resistance rate of H. pylori to metronidazole, suggested that this drug should be excluded from the eradication therapy. However, the resistance rates for tetracycline and clarithromycin did not exceed the established resistance threshold in Colombia. The increased resistance rate of H. pylori to levofloxacin and amoxicillin may partially explain the observed therapeutic failures in Colombia. The phylogenomic tree showed that the H. pylori isolates belong to an own linage (hspColombia). These findings offer valuable insights to enhance the characterization of treatment protocols for the specific H. pylori lineage (hspColombia) at the local level.